2021
DOI: 10.1109/tifs.2020.3029913
|View full text |Cite
|
Sign up to set email alerts
|

Personal Privacy Protection via Irrelevant Faces Tracking and Pixelation in Video Live Streaming

Abstract: To date, the privacy-protection intended pixelation tasks are still labor-intensive and yet to be studied. With the prevailing of video live streaming, establishing an online face pixelation mechanism during streaming is an urgency. In this paper, we develop a new method called Face Pixelation in Video Live Streaming (FPVLS) to generate automatic personal privacy filtering during unconstrained streaming activities. Simply applying multi-face trackers will encounter problems in target drifting, computing effici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 51 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…Utilising the aforementioned object-detection AI algorithms, identification of people and, by extension, faces would allow for this context to be concatenated to the signal and mobility-based gait characteristics, providing the context that the participant was talking while walking. Furthermore, by identifying an individual in that context, the same AI could blur the face of the individual to protect their identity [ 50 , 51 ], upholding ethical concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Utilising the aforementioned object-detection AI algorithms, identification of people and, by extension, faces would allow for this context to be concatenated to the signal and mobility-based gait characteristics, providing the context that the participant was talking while walking. Furthermore, by identifying an individual in that context, the same AI could blur the face of the individual to protect their identity [ 50 , 51 ], upholding ethical concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research indicated that privacy was a core value in system design [29] and people with visual impairments were concerned about their privacy when using technologies [11,21,34]. To protect users' privacy, Zhou et al developed a technology to blur irrelevant people's faces during live-streaming [79]. However, many questions remain unresolved.…”
Section: Design For Inclusive Computer Vision Technologymentioning
confidence: 99%
“…The design of the HDMI's driver reads the frame data from the BRAM through the copy provided by the user() function. Based on this, the data frames can be processed by OpenCV program for face detection and tracking [29].…”
Section: Linux Device Driver Programmingmentioning
confidence: 99%